2012
DOI: 10.2174/156802612805220057
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of Pyrazoline Derivatives As Promising Monoamine Oxidase Inhibitors

Abstract: Among different heterocyclic chemotypes incorporating two nitrogen atoms, pyrazolines could be considered a valid pharmacophore for the synthesis of selective monoamine oxidase (MAO) inhibitors because they were developed by the cyclization of the early hydrazine derivatives such as isocarboxazid. Substituted pyrazolines, decorated with different functional groups, are important lead compounds endowed with a large amount of biological activities. As a matter of this, most of them were also evaluated as dual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Chalcones have been studied extensively for their wide variety of pharmacological activities as antifungal [ 14 ], antimitotic [ 15 ], antitubercular [ 16 ], antitumor and antioxidant [ 17 ], antimalarial [ 18 ] and pyrazolines as these have shown a wide range of biological activities as anti-inflammatory [ 19 , 20 ], antitumor [ 21 ], antitubercular [ 16 ], and monoamino oxidase inhibitor [ 22 ]. Pyrrole is also a vital part of the plant and animal origin as a hemin and vitamin B 12 in animal cells, subunit of chlorophyll in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcones have been studied extensively for their wide variety of pharmacological activities as antifungal [ 14 ], antimitotic [ 15 ], antitubercular [ 16 ], antitumor and antioxidant [ 17 ], antimalarial [ 18 ] and pyrazolines as these have shown a wide range of biological activities as anti-inflammatory [ 19 , 20 ], antitumor [ 21 ], antitubercular [ 16 ], and monoamino oxidase inhibitor [ 22 ]. Pyrrole is also a vital part of the plant and animal origin as a hemin and vitamin B 12 in animal cells, subunit of chlorophyll in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has explored the effect of changes involving mainly positions (N1, C3 and C5) of pyrazoline ring on MAO inhibition [10,11,12,13]. In particular, the N1 position was substituted with an (un)substituted phenyl ring, or acetyl, propanoyl and thiocarbamoyl moieties [14]. These attempts showed that the phenyl, 4-chlorophenyl and propanoyl groups negatively affect inhibitory activity of the hMAO enzymes compared with the acetyl or thiocarbamoyl one.…”
Section: Introductionmentioning
confidence: 99%
“…However, pyrazolines substituted only at the N1 and C3 positions have also been tested [15]. The aryl system on the C3 and C5 positions has been substituted with different groups (halogens, hydroxy, methoxy, methyl) to evaluate how they affect MAO inhibitory activity [14]. Furthermore, the presence of the C5 chiral centre results in the presence of two enantiomers, which could bind and interact differently with the two enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The pyrazole scaffolds are pharmacologically active substances for drug discovery due to their excellent biological and pharmacological activities 31–33 . In our recent works, several pyrazole-containing motifs were designed as potential telomerase inhibitors with anticancer activity 34–36 , selective monoamine oxidase and/or ChE inhibitors for treating Alzheimer’s and Parkinson’s diseases 37 , 38 .…”
Section: Introductionmentioning
confidence: 99%